To Find Out the Relationship Between Levels of Glycosylated Hemoglobin with Meibomian Gland Dysfunction in Patients with Type 2 Diabetes - Fan F; Li X; Li K; Jia Z (Dove Medical Press, 2021)
Fang Fan,1 Xiaodan Li,2 Kejun Li,1 Zhiyang Jia1 1Department of Ophthalmology, Hebei General Hospital, Shijiazhuang, 050051, People's Republic of China; 2Department of Ophthalmology, Shijiazhuang People's Hospital, Shijiazhuang, 050000, People's Republic of ChinaCorrespondence: Zhiyang JiaDepartment of Ophthalmology, Hebei General Hospital, No. 348 Hepingxi Road, Xinhua District, Shijiazhuang, Hebei, 050051, People's Republic of ChinaTel +86-13933120759Email jiazhiyangwork88@163.comAim: The aim of this study was to investigate the relationship between levels of glycosylated hemoglobin (HbA1c) with meibomian gland dysfunction (MGD) in patients with type 2 diabetes mellitus (T2DM) and to further explore the related influencing factors.Methods: Totally, 167 patients with T2DM and 68 non-diabetic subjects were selected. Further, T2DM patients were divided into 2 groups based on 7% HbA1c. Standard patient evaluation of eye dryness (SPEED), lipid layer thickness (LLT), partial blink (PB) ratio, percentage of partial glands (MGP), meibomian gland yielding liquid secretion (MGYLS), meibomian gland yielding secretion score (MGYSS), line of marx (LOM), tear break up time (TBUT), tear meniscus height (TMH) and Schirmer I test (SIT) were applied to evaluate meibomian gland function. Finally, the correlation between HbA1c and various indicators was also analyzed.Results: Between HbA1c≥ 7% group and HbA1c< 7% group, the differences in LLT (P=0.003), MGP (P< 0.001), MGYLS (P=0.014) and TBUT (P=0.015) were all statistically significant. Compared with the non-diabetic group, LLT (P=0.020), MBP (P< 0.001), MGYS (P< 0.001), TBUT (P< 0.001), SIT (P=0.001), TMH (P=0.017) and LOM (P< 0.001) were significantly different in HbA1c≥ 7% group, while the differences of MBP (P=0.031), MGYSS (P< 0.001), SIT (P=0.001) and LOM (P< 0.001) in HbA1c≤ 7% group were statistically significant. Besides, the prevalence of MGD in HbA1c≥ 7% group was evidently higher than that in non-diabetic group (P=0.002). Correlation analysis showed that HbA1c was significantly associated with the LTT and MGP.Conclusion: HbA1c≥ 7% is likely to result in meibomian gland function dysfunctions in T2DM patients, especially related to LLT and MGP.Keywords: diabetes mellitus, type 2 diabetes mellitus, glycosylated hemoglobin, lipid layer thickness, percentage of partial glands